Toxicologic Assessment of a Commercial Decolorized Whole Leaf Aloe Vera Juice, Lily of the Desert Filtered Whole Leaf Juice with Aloesorb - Inder Sehgal; Wallace D. Winters; Michael Scott; Andrew David; Glenn Gillis; Thaya Stoufflet; Anand Nair; Konstantine Kousoulas (Journal of Toxicology)
Aloe vera, a common ingredient in cosmetics, is increasingly being consumed as a beverage supplement. Although consumer interest in aloe likely stems from its association with several health benefits, a concern has also been raised by a National Toxicology Program Report that a nondecolorized whole leaf aloe vera extract taken internally by rats was associated with intestinal mucosal hyperplasia and ultimately malignancy. We tested a decolorized whole leaf (DCWL) aloe vera, treated with activated charcoal to remove the latex portion of the plant, for genotoxicity in bacteria, acute/subacute toxicity in B6C3F1 mice, and subchronic toxicity in F344 rats. We found this DCWL aloe vera juice to be nongenotoxic in histidine reversion and DNA repair assays. Following acute administration, mice exhibited no adverse signs at 3- or 14-day evaluation periods. When fed to male and female F344 rats over 13 weeks, DCWL aloe led to no toxicity as assessed by behavior, stools, weight gain, feed consumption, organ weights, and hematologic or clinical chemistry profiles. These rats had intestinal mucosal morphologies—examined grossly and microscopically—that were similar to controls. Our studies show that oral administration of this DCWL aloe juice has a different toxicology profile than that of the untreated aloe juice at exposures up to 13 weeks.